2010
DOI: 10.1093/toxsci/kfq234
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Aryl Hydrocarbon Receptor–Responsive Genes and Modulation of the Immunoglobulin M Response by 2,3,7,8-Tetrachlorodibenzo-p-Dioxin in Primary Human B Cells

Abstract: Past studies in rodent models identified the suppression of primary humoral immune responses as one of the most sensitive sequela associated with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) exposure. Yet, the sensitivity of humoral immunity to TCDD in humans represents an important toxicological data gap. Therefore, the objectives of this investigation were two-fold. The first was to assess the induction of known aryl hydrocarbon receptor (AHR)-responsive genes in primary human B cells as a measure of early bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 36 publications
6
36
0
Order By: Relevance
“…Approximately 11% (6 of 51) of the donors appeared nonresponsive to TCDD-induced decrease in the number of B cells secreting IgM. This is similar to previously published research (Lu et al, 2010). In contrast to "responsive" donors whose B cells displayed significant suppression at !…”
Section: Tcdd-induced Suppression Of Igm Secretion From Cd40l-activatsupporting
confidence: 86%
See 3 more Smart Citations
“…Approximately 11% (6 of 51) of the donors appeared nonresponsive to TCDD-induced decrease in the number of B cells secreting IgM. This is similar to previously published research (Lu et al, 2010). In contrast to "responsive" donors whose B cells displayed significant suppression at !…”
Section: Tcdd-induced Suppression Of Igm Secretion From Cd40l-activatsupporting
confidence: 86%
“…The number of IgM-secreting cells was quantified by enzymelinked immunospot (ELISPOT) as previously described (Lu et al, 2010). Briefly, multiscreen 96-well filter plates (Millipore, Billerica, Massachusetts) were coated with antihuman IgM antibody (5 lg/ml) (Sigma Aldrich, St. Louis, Missouri) overnight and, subsequently, blocked with 5% bovine serum albumin (Sigma).…”
Section: Enzyme-linked Immunospot Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our data indicated that ITE inhibited B cell differentiation into Ig-producing plasma cells. In previous papers, the highly potent AhR agonist TCDD was shown to suppress the production of IgM in human B cells and a lipopolysaccharide (LPS)-induced transformed mouse B cell line, CH12.LX, and to inhibit the differentiation into Igproducing plasma cells (11,12,20,21). More recently, it was reported that benzo[a]pyrene also suppressed the differentiation into plasma cells in human B cells (2).…”
Section: Discussionmentioning
confidence: 99%